2017
DOI: 10.1016/j.ijsu.2017.06.029
|View full text |Cite
|
Sign up to set email alerts
|

To assess the effects of parathyroidectomy (TPTX versus TPTX+AT) for Secondary Hyperparathyroidism in chronic renal failure: A Systematic Review and Meta-Analysis

Abstract: The findings indicate that TPTX is superior to TPTX + AT, while referring to the rate of recurrent SHPT. However, this conclusion needs to be tested in large-scale confirmatory trials. TPTX seems to be a feasible alternative therapeutic option for the surgical treatment of refractory SHPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 22 publications
0
46
0
1
Order By: Relevance
“…Compared to other procedures, it is associated with a lower recurrence rate, but a higher rate of chronic hypocalcemia and adynamic bone disease [1]. In previous studies, the recurrence rate after total parathyroidectomy varied from 1.9% to 23.8% [12,13]. It is not recommended for patients with CKD stage 5D awaiting kidney transplantation, as the control of serum calcium level may be difficult following the transplantation procedure [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to other procedures, it is associated with a lower recurrence rate, but a higher rate of chronic hypocalcemia and adynamic bone disease [1]. In previous studies, the recurrence rate after total parathyroidectomy varied from 1.9% to 23.8% [12,13]. It is not recommended for patients with CKD stage 5D awaiting kidney transplantation, as the control of serum calcium level may be difficult following the transplantation procedure [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, Tominaga et al [16] reported an increasing frequency of autograft excision over time for the treatment of recurrence in 2,260 patients over a period of 29 years-7.5% required removal of the autograft after 5 years, 17.4% after 10 years, and 25.8% after 20 years. Also, some authors have reported difficulty during autograft excision due to the infiltration of implanted parathyroid tissue into the muscular layers [13].…”
Section: Discussionmentioning
confidence: 99%
“…EPC deficiency and dysfunction may contribute to increased risk of cardiovascular disease (CVD) observed in patients with chronic kidney disease (CKD) [3-6]. Furthermore, EPCs may also be important in the pathogenesis of various kidney disorders including ischemic acute kidney injury (AKI), sepsis, CKD, glomerulonephritis, acute and chronic rejection in patients with renal transplantation (RT).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic renal failure (CRF), a condition frequently attributed to uncontrolled diabetes mellitus and hypertension, has become an economic and public health burden both globally and locally. 1 4 Many studies have demonstrated that CRF is often accompanied by increased inflammatory markers, oxidative stress and thyroid function disorders. 5 9 In addition, patients with CRF often have nonthyroidal illness that frequently manifests with changes in serum thyroid hormone levels, which is known as euthyroid sick syndrome (ESS).…”
Section: Introductionmentioning
confidence: 99%